The resting-state pulse-respiration quotient of humans: lognormally distributed and centred around a value of four - Scholkmann, F; Zohdi, H; Wolf, U (Physiological research, 2019)
The pulse-respiration quotient (heart rate divided by the respiration rate, PRQ = HR/RR) is a parameter capturing the complex state of cardiorespiratory interactions. We analysed 482 single PRQ values obtained from measurement on 134 healthy adult subjects (49 men, 85 women, age: 24.7 ± 3.4, range: 20-46 years) during rest. We found that the distribution of PRQ values (i) has a global maximum at around a value of 4 (median: 4.19) and (ii) follows a lognormal distribution function. A multimodality of the distribution, associated with several PRQ attractor states was not detected by our group-level based analysis. In summary, our analysis shows that in healthy humans the resting-state PRQ is around 4 and lognormally distributed. This finding supports claims about the special role of the 4 to 1 cardiorespiratory coupling in particular and the PRQ in general for physiological and medical views and applications. To the best of our knowledge, our study is the largest conducted so far in healthy adult humans about reference values of the PRQ during a resting-state at day.
Keywords: lidé středního věku; srdeční frekvence; odpočinek; lidé; Adult; Middle Aged; dospělí; Blood Pressure; Female; Reference Standards; Male; ženské pohlaví; mladý dospělý; Heart Rate; Humans; krevní tlak; mužské pohlaví; Respiratory Rate; Young Adult; dechová frekvence; Rest; referenční standardy